Smart IOT-Based Emergency Ambulance System for Rapid Response - Fasate, Shubham; Sawant, Vikas; Ugalmugale, Prathamesh; Gunjal, S. D. (International Journal of Recent Advances in Engineering and Technology, 2025)
In the critical situation of patients for monitoring the health issues and for the purpose of immediate medical services emergency ambulance services facility plays vital role. The proposed system enables real-time detection of emergencies and transmits the victim’s location to the nearest available ambulance. By leveraging this technology, we aim to significantly reduce response time and improve the chances of survival in critical situations. Experimental results demonstrate the effectiveness of the proposed emergency ambulance service application in enhancing the speed and reliability of emergency responses. Emergency detection and response is one of the most promising fields of mobile application development with vast real-life applications. In the real world, the concept is widely used for emergency services, disaster management, and healthcare. The integration of the Internet of Things (IoT) in emergency ambulance services can significantly enhance response times, patient care, and overall efficiency. This paper presents an IoT-based smart ambulance system that leverages real-time data collection, GPS tracking, and smart traffic management to optimize emergency medical response.